Dendrochronology of Ancient Pine Trunks Exposed at the Coastal Bluff: Dating Problems and Possible Causes - Zunde, Māris (Frontiers in Ecology and Evolution, 2022)
Coastal erosion and slumping of the coastal bluff occur at the present day along certain stretches of the Baltic Sea coastal belt in western Latvia. It is considered that the coast currently being eroded consists partly of a cover of wind-blown sand that formed 250–300 years ago. This period saw intensive landward aeolian sand transport as a result of forest cutting and forest fires in the coastal belt and other factors relating to human activity. Within the frame of a short-term research project, dendrochronological dating work was undertaken on the remains of pine trunks discovered at various locations on the coastal bluff that appear to be remains of ancient trees exposed by erosion, with the aim of determining where and when these natural processes occurred. In this particular study, most of the tree trunks could not be dated; however, the potential causes behind the lack of success have been identified. They have been assessed through a comparison of the pattern of variation in annual radial trunk growth for pines growing in the dune belt along the whole of the Latvian seaboard at the present day. Also considered are the previous findings of short-term studies in all three Baltic States on the influence of specific environmental factors on the radial trunk growth of pine. These causes relate to the specific character and variation in the environmental factors significantly affecting the growth of the trees, as well as the slope processes occurring on the coastal bluffs. It is envisaged that the new findings obtained and brought together here will be useful in future, when undertaking or planning dendro-dating work for the purpose of tracing the history of dune migration or assessing the radial growth of pines growing in the dunes.